Comparative study of ultrasound guided fascia iliaca compartment block with femoral nerve block with iPACK in total knee arthroplasty for postoperative analgesia - Dr Deepti Sharma, Dr Arun puri, Dr Jyoti Sharma (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: Significant pain after surgery following total knee arthroplasty (TKA) is usuallycontrolled with regional anaesthetic. Although femoral nerve block (FNB) provides effective painrelief, it may hinder movement because of quadriceps weakness. On the other hand fascia iliacacompartment block (FICB) might offer more or comparable pain alleviation with same or enhancedmotor preservation. In terms of pain management, the usage of rescue analgesics, quadricepsstrength, safety, and patient satisfaction, this study contrasts the effectiveness of continuous FICB+ iPACK (Infiltration between the Popliteal Artery and Capsule of the Knee) with FNB + iPACK